Augmentative and Alternative Communication in Classrooms: Special Education Teacher Competences - Aldabas, Rashed A. (Journal of the American Academy of Special Education Professionals, 2019)
Augmentative and Alternative Communication systems (AAC) are used to support communication abilities of children with severe communication impairments; as a result, teachers should be prepared to teach in their classrooms those students who use AAC. The purpose of this paper is to provide an overview of AAC, in terms of what teachers need to know about AAC, and how to support the use of AAC in classrooms. Finally, this paper discusses teacher competencies in teaching students who use AAC with respect to identification, assessment and implementation AAC. Recommendations and implications for practice are presented.